Water Smart Technologies for Enhancing Corm Yield, Water and Energy Productivity of Elephant Foot Yam (Amorphophallus paeoniifolius) (Dennst.) Nicolson - S., Sunitha; V., Ramesh; J., Suresh Kumar (JOURNAL OF ROOT CROPS, 2019)
Field experiments were carried out at ICAR-Central Tuber Crops Research Institute, Thiruvananthapuram, Kerala during 2017-18 and 2018-19 in Amorphophallus paeoniifolius (Dennst.) Nicolson, commonly known as elephant foot yam, suran or jimmikhand or ole, which is an important tropical tuber crop in India, gaining popularity as a food security crop, and cash crop due to its production potential and preference as a starchy vegetable having high nutritive and medicinal values. Drip irrigation at 50% cumulative pan evaporation (CPE) along with six different sets of water saving techniques, ie., plastic porous ground cover mulching, antitranspirant spray on foliage, soil application of pusa hydrogel, synthetic super absorbent polymer, coir pith and biomulching were experimented. Drip irrigation at 50% CPE, 100% CPE, and a rainfed crop without any water saving measures were kept for comparison. In both the years, the treatment with ground cover mulching resulted in the maximum corm yield (40.1 tha-1), B:C ratio (2.94) and water productivity (3.87 kg m-3), reduced the irrigation water requirement by 50%, enhanced the corm yield by 32% and energy use efficiency by 30% as compared to irrigation at 100% CPE.